Adenomatoid odontogenic tumour: A rare mandibular presentation. (8th January 2016) - Perks, A.C.; Adam, S.; Ahad, S.A.; Patel, M.
Abstract: Adenomatoid odontogenic tumours (AOT) are uncommon, benign tumours that account for about 2–7% of all odontogenic tumours. There is a strong predilection to be found in the maxilla, and predominantly in young females. In this case, we report an unusual finding of an adenomatoid odontogenic tumour in the anterior mandible of a 13‐year‐old male patient. We discuss the radiographic and histological findings, in addition to the surgical management. The AOT is commonly mistaken for a dentigerous cyst, hence the importance of histopathological examination is emphasised. Furthermore, this case report will refresh practitioners on the differential diagnosis of AOT when dealing with lesions of the jaw.